Associations between positive body image and indicators of men's and women's mental and physical health. (March 2015) - Gillen, Meghan M.
Highlights: Positive body image and health indicators among men and women were examined. Positive body image was associated with lower depression and higher self-esteem. Positive body image was associated with less dieting and drive for muscularity. Positive body image was associated with greater skin protection intentions. Results suggest positive body image has health-related benefits for men and women. Abstract: Positive body image has been found to be associated with various beneficial health-related indicators among women. Yet, less is known about its health-related correlates among men. The goal of the current study was to examine associations between positive body image and various mental and physical health-related indicators in both men and women. Undergraduate students ( N  = 284) from a non-residential college in the northeastern United States participated. Individuals with greater positive body image reported less depression, higher self-esteem, fewer unhealthy dieting behaviors, lower drive for muscularity, and greater intentions to protect their skin from UV exposure and damage. Gender did not moderate these associations; thus, connections between positive body image and health-related indicators were similar for women and men. Results suggest that positive body image has significant implications for health and well-being beyond objective body size. Health care providers should encourage positive body image because of its potential health benefits.